2016
DOI: 10.1002/jssc.201600345
|View full text |Cite
|
Sign up to set email alerts
|

Simple high‐performance liquid chromatography method for formaldehyde determination in human tissue through derivatization with 2,4‐dinitrophenylhydrazine

Abstract: A simple high-performance liquid chromatography method has been developed for the determination of formaldehyde in human tissue. FA Formaldehyde was derivatized with 2,4-dinitrophenylhydrazine. It was extracted from human tissue with ethyl acetate by liquid-liquid extraction and analyzed by high-performance liquid chromatography. The calibration curve was linear in the concentration range of 5.0-200 μg/mL. Intra- and interday precision values for formaldehyde in tissue were <6.9%, and accuracy (relative error)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…A method of headspace gas chromatography revealed that the concentrations of FA in human urine were between 0.019 and 0.048 mM [34]. Moreover, the endogenous FA concentrations in brain samples of control mice detected in the current study were approximately 0.27 mM, which is consistent with the previous reports using HPLC-Fluo [20], HPLC-UV [19], and GC–MS [17]. …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A method of headspace gas chromatography revealed that the concentrations of FA in human urine were between 0.019 and 0.048 mM [34]. Moreover, the endogenous FA concentrations in brain samples of control mice detected in the current study were approximately 0.27 mM, which is consistent with the previous reports using HPLC-Fluo [20], HPLC-UV [19], and GC–MS [17]. …”
Section: Discussionsupporting
confidence: 90%
“…The earliest determination method for measuring FA in brain tissues (~0.16–0.24 mM) was carried out using gas chromatography/mass spectrometry (GC–MS) [17]. Another sensitive method, developed for the detection of FA in the liver, utilized high-performance liquid chromatography with an ultra violet detector (HPLC-UV) [18, 19]. More recently, using a high-performance liquid chromatography with a fluorescence detector (HPLC-Fluo), we found that there was 0.25–0.32 mM FA in the hippocampi of normal adult mice and rats [20].…”
Section: Introductionmentioning
confidence: 99%
“…DNPH derivatization and HPLC-UV analysis are used in environmental monitoring of air and water quality and used for screening and monitoring carbonyl compounds in various matrices by the US federal agencies (Table 1) [119,133,134,135,136,137]. The HPLC-UV technique is also being used in the food industry to measure aldehydes in food and beverages [39,138,139,140,141,142] and in biomedical research to measure aldehydes and carbonyls in various matrices such as urine, plasma and serum samples [40,143,144,145,146,147,148,149,150,151,152]. DNPH derivatization is also used in conjunction with a reducing agent, 2-picoline borane (2-PB) to stabilize carbonyl-hydrazones and to resolve isomeric compounds produced during the reaction that might interfere with subsequent quantitative analysis by HPLC-UV [153].…”
Section: Bioanalytical and Mass Spectrometric Methods For Charactementioning
confidence: 99%
“…This approach is useful for characterizing carbonyls in air samples for environmental analysis as well as for the characterization of other α,β-unsaturated aldehydes in tobacco smoke. DNPH derivatization was also used for the analysis and measurement of acetaldehyde in plasma and red blood cells [154], formaldehyde determination in human tissue [151], carbonyl compounds in exhaled breath of e-cigarette users [35], and for the measurement of formaldehyde released from heated hair straightening cosmetic products [18]. Other reagents such as the previously mentioned 2-thiobarbituric acid (2-TBA) and diaminonapththalene (DAN) are also being used for HPLC-UV analysis of carbonyl compounds from biological matrices and environmental samples [155,156,157].…”
Section: Bioanalytical and Mass Spectrometric Methods For Charactementioning
confidence: 99%
“…In the search for new natural radical-scavenging reactive molecule, complex mixtures interferences are frequently encountered. The developed methods involving free radical reactive molecule assays coupled with HPLC were successfully developed [11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%